Consumer Acceptance on Chocolate Drink Made with a Mixture of Commercial Cocoa Powder and Unfermented Cocoa Powder - Laras Cempaka; Tubagus Emir Abdul Hakim; Wayudi David (Indonesian Coffee and Cocoa Research Institute, 2021)
Cocoa is one of the foods that contains polyphenol-rich compounds that act as antioxidants. The processing of cocoa into chocolate products generallycauses a decrease in the number of polyphenols. In the development of chocolate beverage products, it is necessary to evaluate sensory evaluation. The purposeof this study was to determine consumer acceptance, total phenolic content (TPC) and antioxidant activity of chocolate drinks made from commercial cocoa powderadded with unfermented cocoa powder. Seventy-five panellist (17-23 years old) contributed to the consumer acceptance of four samples of chocolate drinks witha ratio of commercial cocoa powder: unfermented cocoa powder = 100%:0%, 90%:10%, 80%:20%, 70%:30%. The sample than was analyzed for its antioxidantactivity using the ascorbic acid equivalent antioxidant capacity and total phenolic content using the Folin-Ciocalteau method. The results showed that the sample witha composition of 100% commercial fermented cocoa had the highest value on each sensory attribute. It had the highest TPC (321.235 mg gallic acid equivalent),antioxidant activity (982 ppm), and inhibition percentage (46%), respectively. Addition of the unfermented cocoa powder composition showed a decrease in the level ofconsumer preference. However, the addition did not significantly affect the total phenolic content, but slightly increased the antioxidant activity. The use of unfermentedcocoa powder for mixing components that are not processed standardly has not been well received by consumers, proper processing of unfermented cocoa powderis required if the polyphenol compound is desired.